Breaking barriers: challenging the notion of a strong link between physical fitness and executive functions in 10-year-olds - Filip Kojić; Anđela Šoškić; Ivana Radin; Danimir Mandić; Gabrijela Grujić; Saša Đurić (BMC Pediatrics)
Abstract Background This study utilized a replicated measurement approach to comprehensively explore the connections between various aspects of physical fitness and executive functions in prepubescent children. Methods The sample consisted of 62 students (32 boys, 30 girls, aged 10.44 ± 0.33 years) with assessments of physical fitness and executive functions conducted at two time points 4 months apart. Physical fitness assessment involved evaluating body composition (body-mass index, fat mass, fat-free mass) and measures of motor coordination (Obstacle Course Backward test), strength (Long Standing Jump test), speed of movement (Plate Tapping test), and aerobic fitness (20 m Shuttle Run test). Executive functions, specifically inhibition and cognitive flexibility, were evaluated using the Modified Stroop task and Trail Making task, respectively. Results Initial measurements showed only low correlations (r = 0.12–0.20) between the Plate Tapping and Shuttle Run with executive function tasks, which did not reach statistical significance, while other connections were consistently trivial. In the follow-up measurement, the Plate Tapping test showed a moderate correlation (r = 0.39) with the Stroop task, while remaining correlations were either negligible or low and not significant. The findings suggest two important conclusions: (i) body composition shows limited association with executive functions in children; (ii) among motor variables, only the speed of limb movement may have some relevance for inhibition, but this association is relatively modest and inconsistent. Conclusions Overall, the morphological status and motor competence of prepubertal children seem to have minimal effects on cognitive tasks involving inhibition and cognitive flexibility, and vice versa.